The FBXW7‐NOTCH interactome: A ubiquitin proteasomal system‐induced crosstalk modulating oncogenic transformation in human tissues. Issue 4 (6th April 2021) - Kar, Rohan; Jha, Saurabh Kumar; Ojha, Shreesh; Sharma, Ankur; Dholpuria, Sunny; Raju, Venkata Sita Rama; Prasher, Parteek; Chellappan, Dinesh Kumar; Gupta, Gaurav; Kumar Singh, Sachin; Paudel, Keshav Raj; Hansbro, Philip M.; et al.
Abstract: Background: Ubiquitin ligases or E3 ligases are well programmed to regulate molecular interactions that operate at a post‐translational level. Skp, Cullin, F‐box containing complex (or SCF complex) is a multidomain E3 ligase known to mediate the degradation of a wide range of proteins through the proteasomal pathway. The three‐dimensional domain architecture of SCF family proteins suggests that it operates through a novel and adaptable "super‐enzymatic" process that might respond to targeted therapeutic modalities in cancer. Recent findings: Several F‐box containing proteins have been characterized either as tumor suppressors (FBXW8, FBXL3, FBXW8, FBXL3, FBXO1, FBXO4, and FBXO18) or as oncogenes (FBXO5, FBXO9, and SKP2). Besides, F‐box members like βTrcP1 and βTrcP2, the ones with context‐dependent functionality, have also been studied and reported. FBXW7 is a well‐studied F‐box protein and is a tumor suppressor. FBXW7 regulates the activity of a range of substrates, such as c‐Myc, cyclin E, mTOR, c‐Jun, NOTCH, myeloid cell leukemia sequence‐1 (MCL1), AURKA, NOTCH through the well‐known ubiquitin‐proteasome system (UPS)‐mediated degradation pathway. NOTCH signaling is a primitive pathway that plays a crucial role in maintaining normal tissue homeostasis. FBXW7 regulates NOTCH protein activity by controlling its half‐life, thereby maintaining optimum protein levels in tissue. However, aberrations in the FBXW7 or NOTCH expression levels can lead to poor prognosis and detrimental outcomes in patients. Therefore, the FBXW7‐NOTCH axis has been a subject of intense study and research over the years, especially around the interactome's role in driving cancer development and progression. Several studies have reported the effect of FBXW7 and NOTCH mutations on normal tissue behavior. The current review attempts to critically analyze these mutations prognostic value in a wide range of tumors. Furthermore, the review summarizes the recent findings pertaining to the FBXW7 and NOTCH interactome and its involvement in phosphorylation‐related events, cell cycle, proliferation, apoptosis, and metastasis. Conclusion: The review concludes by positioning FBXW7 as an effective diagnostic marker in tumors and by listing out recent advancements made in cancer therapeutics in identifying protocols targeting the FBXW7‐NOTCH aberrations in tumors.